Conceptualizing vitality at work: Bridging the gap between individual and organizational health - Sania Zahra Malik; Robert MacIntosh; Robert McMaster (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
Based on the emerging literature on positivity in behavioral and organizational sciences, this study conceptualizes the phenomenon of Vitality at Work (VAW). VAW is an integrative, multi-dimensional framework which combines personal health with positive work attitudes and an energizing work environment. The article proposes that VAW is a state in which individuals feel healthy and committed to their work and organizations in the presence of positive and energizing work connections. Moreover, these three dimensions exist in a symbiotic relationship with each other. By demonstrating this coexistence, VAW confirms the interdependence of individual and organizational health. Five factors were identified from literature as the underlying dimensions of VAW which are; Sense of Coherence (SoC); Perceived Health and Energy (PHE); Energizing Connections (EC); Organizational Commitment (OC); and Goal Commitment (GC). For the first time, these elements have been brought together in a single empirical model, which applies exploratory factor analysis and confirmatory factor analysis to survey data on academics employed in top-ranking United Kingdom's (UK) universities. Results from 365 responses on a structured questionnaire demonstrate the robustness of the proposed construct, and provide evidence that healthy employees are committed to their work and organizations when energized by positive work connections.
Keywords: 330; energizing connections; health; positive psychology; sense of coherence; vitality at work; well-being